The diversity and evolution of ion channels - Jegla, Tim (Henry Stewart Talks, 2011)
What are ion channels and why are they important?, Ion channels have diverse selectivity and gating, Human channel diversity and structures, A fundamental set of ion channels in animals, How our voltage-gated ion channels evolved, How are our ion channel gene families made?